VEGF-C expression in oral cancer by neurotransmitter-induced activation of beta-adrenergic receptors - Vilardi, Bruna Maria Rodrigues; Bravo-Calderón, Diego Mauricio; Bernabé, Daniel Galera [UNESP]; Oliveira, Sandra Helena Penha de [UNESP]; Oliveira, Denise Tostes (Springer Nature, 2013)
The aim of this study was to investigate the expression of vascular endothelial growth factor type C (VEGF-C) in oral squamous cell carcinoma (OSCC) cell lines through norepinephrine-induced activation of beta-adrenergic receptors. Human OSCC cell lines (SCC-9 and SCC-25) expressing beta-adrenergic receptors were stimulated with different concentrations of norepinephrine (0.1, 1, and 10 μM) and 1 μM of propranolol, and analyzed after 1, 6, and 24 h. VEGF-C gene expression and VEGF-C production in the cell supernatant were evaluated by real-time PCR and by ELISA, respectively. The results showed that beta-adrenergic receptor stimulation by different concentrations of norepinephrine or blocking by propranolol did not markedly alter VEGF-C expression by SCC-9 and SCC-25 cells. VEGF-C protein levels produced by oral malignant cell lines after stimulation with different norepinephrine concentrations or blocking with propranolol was statistically similar (p > 0.05) to those of the control group (nonstimulated OSCC cell lines). Our findings suggest that stimulation of beta-adrenergic receptors by means of norepinephrine does not seem to modulate the VEGF-C expression in OSCC cell lines. These findings reinforce the need for further studies in order to understand the responsiveness of oral cancer to beta-adrenergic receptor stimulation or blockage, especially with regard to VEGF-C production. © 2012 International Society of Oncology and BioMarkers (ISOBM).
Keywords: Adrenergic receptors; Oral cancer; VEGF; beta adrenergic receptor; noradrenalin; propranolol; vasculotropin C; cancer cell; cancer cell culture; cell line SCC 25; cell line SCC 9; controlled study; enzyme activation; enzyme activity; enzyme synthesis; human; human cell; in vitro study; mouth squamous cell carcinoma; priority journal; protein analysis; protein expression; protein function; Adrenergic beta-Antagonists; Carcinoma, Squamous Cell; Cell Line, Tumor; Humans; Mouth Neoplasms; Neurotransmitter Agents; Norepinephrine; Propranolol; Receptors, Adrenergic, beta; Vascular Endothelial Growth Factor C